New Hybrid EEM/BEM Method for Ellipsoidal Electrets Determination - Novakovic, I. M.; Aleksic, S. R.; Raicevic, N. B. (Elektronika ir Elektrotechnika, 2013)
Precise numerical calculations are essential in the modeling and design of the electrets, and in choosing the electret manufacturing technology. It is necessary to optimize various parameters, including arrangement of the high voltage needles and the grids. In combination with Equivalent Electrodes Method, one novel numerical method, so called Hybrid Boundary Elements Method, is proposed in this paper. An arbitrary shaped boundary between two dielectrics can be replaced by equivalent charges, located at the dielectrics boundary. It is possible, by using boundary conditions, to form a system of equations. By solving this system, the unknown polarized charges can be determined. Electrostatic field distribution both inside and outside the electrets were determined by using our method. The obtained results were compared with a commercial software (FEM) results and some analytical data. The results are in a good agreement. DOI: http://dx.doi.org/10.5755/j01.eee.19.3.3217